El conocimiento tributario y su relación con la evasión del Impuesto a la Renta en Empresas constructoras del distrito de San Isidro en Lima, 2021 - Gallo Alvarez, Jose Pablo (2024)
The objective of this research was to determine the relationship between tax knowledge and Third Category Income Tax evasion in construction companies in the San Isidro district of Lima, 2021. For this purpose, a methodology with a mixed approach, descriptive level, non-experimental design and correlational scope was used. For the qualitative approach, we worked with a sample of three experts, to whom an interview guide was applied as an instrument. For the quantitative approach, a population of 54 construction companies in the San Isidro District for the year 2021 was considered, from which a sample of 23 companies was selected, to whom two questionnaires of the variables studied (tax knowledge and tax evasion) were applied as an instrument, with structured questions with Likert-type rating scales. The results show the existence of a considerable positive correlation of 0.737 between tax knowledge and tax evasion, with a p-value of 0.000<0.05 and, in effect, it is concluded that tax knowledge is significantly related to tax evasion in construction companies in the San Isidro district of Lima, 2021. The execution of tax training programs aimed at children, young people and university students is recommended as they are future entrepreneurs and business collaborators, that is, income-generating citizens.